Late mortality after sepsis: propensity matched cohort study. (17th May 2016) - Prescott, Hallie C; Osterholzer, John J; Langa, Kenneth M; Angus, Derek C; Iwashyna, Theodore J
Abstract : Objectives To determine whether late mortality after sepsis is driven predominantly by pre-existing comorbid disease or is the result of sepsis itself. Deign Observational cohort study. Setting US Health and Retirement Study. Participants 960 patients aged ≥65 (1998-2010) with fee-for-service Medicare coverage who were admitted to hospital with sepsis. Patients were matched to 777 adults not currently in hospital, 788 patients admitted with non-sepsis infection, and 504 patients admitted with acute sterile inflammatory conditions. Main outcome measures Late (31 days to two years) mortality and odds of death at various intervals. Results Sepsis was associated with a 22.1% (95% confidence interval 17.5% to 26.7%) absolute increase in late mortality relative to adults not in hospital, a 10.4% (5.4% to 15.4%) absolute increase relative to patients admitted with non-sepsis infection, and a 16.2% (10.2% to 22.2%) absolute increase relative to patients admitted with sterile inflammatory conditions (P<0.001 for each comparison). Mortality remained higher for at least two years relative to adults not in hospital. Conclusions More than one in five patients who survives sepsis has a late death not explained by health status before sepsis.